Ticagrelor or Prasugrel in Patients With ST-Segment–Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention. Issue 24 (15th December 2020) - Aytekin, Alp; Ndrepepa, Gjin; Neumann, Franz-Josef; Menichelli, Maurizio; Mayer, Katharina; Wöhrle, Jochen; Bernlochner, Isabell; Lahu, Shqipdona; Richardt, Gert; Witzenbichler, Bernhard; Sibbing, Dirk; Cassese, Salvatore; et al.
Abstract : Background: Data on the comparative efficacy and safety of ticagrelor versus prasugrel in patients with ST-segment–elevation myocardial infarction undergoing primary percutaneous coronary intervention are limited. We assessed the efficacy and safety of ticagrelor versus prasugrel in a head-to-head comparison in patients with ST-segment–elevation myocardial infarction undergoing primary percutaneous coronary intervention. Methods: In this prespecified subgroup analysis, we included 1653 patients with ST-segment–elevation myocardial infarction randomized to receive ticagrelor or prasugrel in the setting of the ISAR REACT-5 trial (Intracoronary Stenting and Antithrombotic Regimen: Rapid Early Action for Coronary Treatment 5). The primary end point was the incidence of death, myocardial infarction, or stroke at 1 year after randomization. The secondary end point was the incidence of bleeding defined as BARC (Bleeding Academic Research Consortium) type 3 to 5 bleeding at 1 year after randomization. Results: The primary end point occurred in 83 patients (10.1%) in the ticagrelor group and in 64 patients (7.9%) in the prasugrel group (hazard ratio, 1.31 [95% CI, 0.95–1.82]; P =0.10). One-year incidence of all-cause death (4.9% versus 4.7%; P =0.83), stroke (1.3% versus 1.0%; P =0.46), and definite stent thrombosis (1.8% versus 1.0%; P =0.15) did not differ significantly in patients assigned to ticagrelor or prasugrel. One-year incidence of myocardial infarction (5.3% versus 2.8%; hazard ratio, 1.95 [95% CI, 1.18–3.23]; P =0.010) was higher with ticagrelor than with prasugrel. BARC type 3 to 5 bleeding occurred in 46 patients (6.1%) in the ticagrelor group and in 39 patients (5.1%) in the prasugrel group (hazard ratio, 1.22 [95% CI, 0.80–1.87]; P =0.36). Conclusions: In patients with ST-segment–elevation myocardial infarction undergoing primary percutaneous coronary intervention, there was no significant difference in the primary end point between prasugrel and ticagrelor. Ticagrelor was associated with a significant increase in the risk for recurrent myocardial infarction. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01944800. Abstract : Supplemental Digital Content is available in the text.